Achene characteristics of Turkish Centaurea (Asteraceae) and their systematic application - Bona, Mehmet (Bangladesh Journal of Botany, 2015)
This article investigates the exomorphic characteristics of the achenes which are achene size, color, and surface pattern, and pappus length, and colour. All these characteristics in seven taxa of Asteraceae namely, C. aggregata Fisch. & C.A. Mey. ex DC. subsp. aggregata, C. sivasica Wagenitz, C. polypodiifolia Boiss. var. polypodiifolia, C. polypodiifolia Boiss. var. szowitziana (Boiss.) Wagenitz, C. iberica Trev. ex Spreng, C. urvillei DC. subsp. stepposa Wagenitz, and C. carduiformis DC. subsp. carduiformis var. carduiformis in are described, illustrated and compared. The results of SEM at higher magnification showed three types of achene surface patterns: glebulate-ruminate, smooth, and rugose. In these patterns, there were diagnostic characteristics and differences at the specific level for Centaurea. A key to the taxa has been provided on the basis of these achene characteristics. DOI: http://dx.doi.org/10.3329/bjb.v43i2.21668 Bangladesh J. Bot. 43(2): 163-168, 2014 (September)